Preparation method of ultrahigh-temperature EB-PVD thermal barrier coating
By performing a multivariate high entropy design of zirconate and preparing high entropy zirconate ceramic coating using EB-PVD method, the problem of high thermal conductivity of the existing EB-PVD thermal barrier coating at high temperatures is solved, and a thermal barrier coating with low thermal conductivity and high phase stability is achieved, which extends the service life of the coating.
Patent Information
- Application Number
- CN202411992508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing EB-PVD thermal barrier coating has high thermal conductivity at high temperatures, resulting in poor thermal insulation ability and prone to phase change, which in turn affects the service life of the coating.
By performing a multivariate high-entropy design of traditional zirconates, a high-entropy structure EB-PVD target was prepared, and a high-entropy zirconate ceramic coating was deposited on the surface of the high-temperature alloy matrix using the EB-PVD method to form a thermal barrier coating with low thermal conductivity and high phase stability.
A thermal barrier coating with low thermal conductivity and stable phase structure at high temperatures is achieved, which extends the service life of the coating and matches well with the thermal expansion coefficient of the matrix material.
Smart Images

Figure CN119751060A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-temperature thermal protective coatings and relates to a method for preparing an ultra-high temperature EB-PVD thermal barrier coating (TBC). Background Art
[0002] As a common thermal protection technology, thermal barrier coatings provide thermal insulation protection for metal substrates to protect them from the influence of high-temperature gases. Thermal barrier coatings are mainly deposited on the surface of alloy substrates (mainly high-temperature alloys) by atmospheric plasma spraying (APS) and electron beam physical vapor deposition (EB-PVD). Different deposition methods will produce thermal barrier coatings with different structures, which will affect their performance. In order to increase the matching degree between the substrate and the ceramic surface layer and reduce the thermal expansion during use, a layer of metal bonding layer material is usually required. The materials used to form thermal barrier coatings include NiCoCrAlY, NiCrAlY, NiAl, etc. as bonding layer materials, and yttria-stabilized zirconia ceramics (YSZ), alumina and other advanced ceramic raw materials as surface layer materials. According to the different material states, the coating preparation can be divided into gaseous process, solution state process, molten or semi-molten state process and solid state process. The processes corresponding to the gaseous process are mainly physical vapor deposition (PVD) and chemical vapor deposition (CVD). In recent years, EB-PVD technology has many advantages, such as high evaporation and deposition rate, dense coating, easy and precise control of chemical composition, columnar crystal structure, no pollution, high thermal efficiency, strong bonding between substrate and film, etc. It has been widely used in national defense and civilian fields. -3Pa vacuum, its preparation process is firstly to heat the raw material to a gasified state by a high energy density electron beam, and then the gasified material grows into columnar crystals through continuous deposition on the pre-treated substrate surface under the action of the deflection magnetic field. The coating prepared by the EB-PVD method has a high bonding strength with the base, can withstand high external tensile or bending stress, and has good thermal shock resistance, which greatly increases the life of the coating, which is about 7 times that of the APS coating. The thermal barrier coating prepared by the EB-PVD method is mainly used on the rotating parts of turbine engines, such as turbine blades and rotating shafts. Due to the dense structure of the EB-PVD coating, its thermal conductivity is significantly higher than that of the plasma coating. For thermal barrier coatings, higher thermal conductivity is very unfavorable, which has a great negative impact on the thermal insulation ability of thermal barrier coatings. Higher thermal conductivity is bound to affect the further application of EB-PVD thermal barrier coatings. The most widely used ceramic coating material in the field of EB-PVD coatings is 6-8wt% yttria stabilized zirconia (YSZ). YSZ coatings are usually prepared by EB-PVD and APS. In particular, the introduction of columnar structure by EB-PVD can improve strain compliance and withstand long-term operation below 1150°C. However, the YSZ coating sintered and phase changed severely, resulting in TBC failure (>1200°C). Moreover, the coating prepared by EB-PVD has poor thermal insulation effect due to its inherent columnar crystal structure. In order to improve the shortcomings of EB-PVD in the preparation of thermal barrier coatings, new ceramic materials with lower thermal conductivity are used to replace the current YSZ. Seeking new ceramic materials with lower thermal conductivity to replace YSZ is one of the current research hotspots in the field of thermal barrier coatings.
[0003] For the above reasons, it is necessary to develop new ceramic materials with low thermal conductivity and high thermal stability. Rare earth oxide-stabilized ZrO2, pyrochlore materials, perovskite oxides and aluminates have been widely studied as possible successors to YSZ. Among them, pyrochlore materials have been studied most intensively. In particular, A2B2O7 ceramic materials have the performance advantages of high melting point (>2000℃) and low thermal conductivity (1.56W / (m·K) at 1000℃).
[0004] The multi-component high-entropy design of ceramics is believed to be able to solve the material selection problem of thermal barrier coatings at higher temperatures. It is reported that high-entropy ceramics have outstanding comprehensive properties and can make up for the shortcomings of single-component TBCs materials. Studies have shown that multi-component high-entropy design enables high-entropy ceramics to have high-entropy effect, lattice distortion effect, cocktail effect and hysteresis diffusion effect, which makes high-entropy ceramics have relatively higher phase stability, lower thermal conductivity, performance adjustability and better high-temperature mechanical properties. Current research shows that A2B2O7 (A represents rare earth elements) is the most promising new ceramic material for thermal barrier coatings, but there are few reports on the preparation and performance of thermal barrier coatings corresponding to this system material.
[0005] At present, most of the research is focused on the ceramic material itself, and there is no report on high-entropy EB-PVD targets and their coatings. Because when the coating material composition of EB-PVD technology is complex, it becomes difficult to control the composition of the material, which also makes it difficult to apply high-entropy ceramic materials in the field of EB-PVD coatings. In addition, when preparing high-entropy ceramic targets, solid-phase synthesis is required first, and then the target material is sintered to ensure density. Its various rare earth oxides are difficult to ensure uniformity and the complexity of the process limits the development of high-entropy EB-PVD coatings. Summary of the invention
[0006] In view of the problems that the thermal barrier effect of existing EB-PVD thermal barrier coatings is not as good as that of APS thermal barrier coatings of the same level, phase change is easy to occur, and the high-temperature thermal conductivity leads to failure of the coating in service, the present invention provides a method for preparing an ultra-high temperature EB-PVD thermal barrier coating. The present invention provides a high-entropy structure EB-PVD target material by multi-element high-entropy design of traditional zirconates, and prepares the coating by EB-PVD method. The prepared coating has good high-temperature phase stability, a thermal expansion coefficient that is more matched with the substrate material, and extremely low high-temperature thermal conductivity, which can replace the currently used single-system EB-PVD material, improve the high-temperature stability of rare earth zirconate thermal barrier coatings, and extend their service life.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing an ultra-high temperature EB-PVD thermal barrier coating comprises the following steps:
[0009] Step 1: Add zirconium oxide grinding balls and appropriate amount of deionized water to the vertical ball mill, then add a certain amount of dispersant to the deionized water, and after the dispersant is completely dissolved, follow the (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7(SETDL) shown in the ratio, add nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder, after ball milling for a period of time, add a certain amount of binder and continue ball milling for a period of time to obtain a uniform slurry, wherein:
[0010] The particle size of the nano Sm2O3 powder is 5 to 90 nm;
[0011] The particle size of the nano-Eu2O3 powder is 5 to 90 nm;
[0012] The particle size of the nano Tb2O3 powder is 5 to 90 nm;
[0013] The particle size of the nano Dy2O3 powder is 5 to 90 nm;
[0014] The particle size of the nano Lu2O3 powder is 5 to 90 nm;
[0015] The particle size of the nano ZrO2 powder is 5 to 90 nm;
[0016] The raw materials of the nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are of 4N grade purity;
[0017] The amount of deionized water used is 0.5 to 3 times the total mass of the nanopowder;
[0018] The dispersant is sodium tripolyphosphate (Na5P3O 10 ), sodium hexametaphosphate ((NaPO3)6), sodium pyrophosphate (Na4P2O7), ammonium citrate (C6H5O7(NH4)3), sodium citrate (C6H5Na3O7), polyvinyl alcohol (PVA), polyethylene glycol (PEG), etc. One or more of the dispersant, the amount of which is 0.03-6% of the total mass of the nanopowder;
[0019] The diameter of the zirconia grinding ball is 2 to 10 mm, the amount of the zirconia grinding ball is 1 to 5 times the total mass of the nano powder, the total ball milling time is 6 to 24 hours, and the number of revolutions is 300 to 1000 revolutions per minute;
[0020] The binder is one of gum arabic (Acacia), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), tetraethyl orthosilicate (TEOS), etc., and the amount of the binder is 0.1-10% of the total mass of the nano powder;
[0021] Step 2: The slurry obtained in step 1 is subjected to spray granulation to obtain micrometer-sized nanostructured spherical rare earth oxide powder, wherein:
[0022] The parameters of the spray granulation are as follows: the air inlet temperature is set at 200-250°C, the air outlet temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45r / min, and the needle passing speed is set at 10-15t / min;
[0023] Step 3: The rare earth oxide powder obtained in step 2 is screened according to the particle size, the screened spherical powders with different particle sizes are proportioned, and then pressed by cold isostatic pressing to obtain target embryos with different porosities, wherein:
[0024] The sieving specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, and the mass ratio is 2-6:1-3:1-5, and is used according to the particle size distribution of the granulated powder and its different porosity requirements;
[0025] During the pressing process, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 s.
[0026] The cold isostatic pressing method can use wet bag cold isostatic pressing, dry bag cold isostatic pressing, press pre-pressing and other molding methods. Preferably, the cold isostatic pressing method is wet bag cold isostatic pressing;
[0027] Step 4: Sinter the target green body to obtain the SETDL high entropy zirconate EB-PVD target, wherein:
[0028] The sintering mechanism is as follows: first, the temperature is raised to 350°C (debinding temperature) at 1-10°C / min and kept for 300-420min, then, the temperature is raised to 1100°C at 1-10°C / min and kept for 180-250min, then, the temperature is raised to 1400°C (synthesis temperature) at 1-10°C / min and kept for 480-600min, and finally, the temperature is lowered to room temperature;
[0029] The debinding temperature is related to the types of dispersants and glue used in granulation, and the synthesis temperature is related to different high entropy systems;
[0030] Step 5: The surface of the high-temperature alloy substrate is polished and leveled, and then sandblasted to prepare a certain degree of roughness on the surface. Then, acetone and ethanol are used to ultrasonically clean the substrate, and after drying, an alloy bonding layer (MCrAlX) is prepared on the surface by thermal spraying technology, wherein:
[0031] The high temperature alloy substrate may be one of nickel-based, cobalt-based, iron-based and other high temperature alloys;
[0032] The thermal spraying technology may be one of atmospheric plasma spraying (APS), low pressure plasma spraying (LPPS), and high velocity oxygen fuel (HVOF);
[0033] The alloy bonding layer may be NiCrAlY, CoCrAlY, NiCoCrAlY, etc.;
[0034] Step 6: Deposit the high entropy zirconate EB-PVD target on the surface of the MCrAlY alloy bonding layer obtained in step 5 by vapor deposition to form a SETDL high entropy zirconate ceramic coating, thereby obtaining an ultra-high temperature EB-PVD thermal barrier coating having a single ceramic layer coating system with low thermal conductivity and good matching with the thermal expansion coefficient of the substrate, wherein:
[0035] The parameters in the preparation process of the SETDL high entropy zirconate ceramic coating are as follows: the substrate temperature is heated from room temperature to 600-850°C, the distance between the substrate and the evaporation target (target-substrate distance) and the angle between the substrate plane normal and the deposition incident steam particles (incident angle) can be adjusted according to actual needs, the maximum target-substrate distance is 500 mm, and the incident angle is set to 45°. During the coating preparation process, the electron acceleration voltage is 20-25 kV, and the vacuum degree is less than 1×10 -2 Pa, the deposition rate is controlled by controlling the electron beam flow and adjusting the size of the evaporation target molten pool. The deposition rate can reach up to 1-10 μm / min, and the deposition coating thickness is 100-500 μm.
[0036] The vapor deposition method may be a surface protection preparation process such as electron beam physical vapor deposition (EB-PVD) and physical vapor deposition (PVD).
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. The present invention utilizes nano-powder regranulation technology and cold isostatic pressing technology to prepare SETDL high-entropy zirconate as a target material suitable for electron beam physical vapor deposition, providing a method for the implementation of this high-performance high-entropy material on thermal spray coatings.
[0039] 2. The present invention utilizes particle size classification and blending technology to press spherical powder of rare earth oxide into green embryos. In order to ensure that the overall volume shrinkage of the target material is minimized and has a certain porosity requirement, the solid phase synthesis sintering route is combined with the target material sintering route. The porosity and volume shrinkage can be strictly controlled, and the problems of unstable size of the target material after sintering and the need for subsequent turning processing are solved. The target material preparation process is simplified and the production cost is reduced.
[0040] 3. The SETDL target material prepared by the present invention has high purity, excellent mechanical properties, and a smooth coating surface structure, and can be used to replace traditional EB-PVD coating materials as high-performance thermal barrier coating materials for aircraft engines and gas turbines.
[0041] 4. The present invention uses EB-PVD technology for the first time to prepare SETDL high-entropy zirconate thermal barrier coatings, which breaks through the problem that the vapor-deposited high-entropy coatings are prone to phase structure decomposition and rare earth element segregation under the influence of saturated vapor pressure. The high-entropy EB-PVD thermal barrier coating has a columnar crystal structure with several pores between the columnar crystals. The high-entropy EB-PVD thermal barrier coating has good stability in phase, structure and composition under high-temperature service conditions of 1700°C, and still maintains the pyrochlore phase, without element segregation and precipitation. The present invention has the advantages of high energy, wide range of material applications, easy operation, high deposition efficiency, and easy industrialization.
[0042] 5. The present invention solves the problem of poor thermal barrier effect caused by the EB-PVD coating structure. The prepared coating has low thermal conductivity at high temperature, stable phase structure, and good thermal expansion coefficient matching with the base alloy. It can replace the existing dual ceramic coating system as a thermal barrier coating and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the process flow chart of the preparation of SETDL high entropy zirconate EB-PVD target and ultra-high temperature EB-PVD thermal barrier coating;
[0044] Figure 2 This is a macroscopic structure diagram of the target material after sintering in Example 1;
[0045] Figure 3 is a cross-sectional structure diagram of the target material in Example 1;
[0046] Figure 4 It is the surface morphology and energy spectrum of the molten pool solidification after the target material evaporates in Example 1;
[0047] Figure 5 This is a comparison diagram of the XRD of the target material molten pool, coating, and original target material in Example 1;
[0048] Figure 6 is a cross-sectional view of the coating prepared by EB-PVD in Example 1;
[0049] Figure 7 Surface image of the coating prepared by EB-PVD in Stone Example 1. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0051] Embodiment 1:
[0052] This embodiment provides a method for preparing an ultra-high temperature EB-PVD thermal barrier coating, wherein five rare earth oxides, namely nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder, and zirconium oxide are firstly sprayed to obtain target raw material powders; spherical powders with different particle size ratios are obtained by screening, and target green embryos are made by cold isostatic pressing, and then the green embryo target material is sintered; and a high entropy zirconate ceramic coating is deposited on the surface of a sample coated with a bonding layer by electron beam physical vapor deposition (EB-PVD) technology. Specifically, it is achieved by the following steps:
[0053] Step 1: According to (Sm0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7, nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are weighed, wherein: the particle size of the nano Sm2O3 powder is 20nm; the particle size of the nano Eu2O3 powder is 20nm; the particle size of the nano Tb2O3 powder is 20nm; the particle size of the nano Dy2O3 powder is 20nm; the particle size of the nano Lu2O3 powder is 20nm; the particle size of the nano ZrO2 powder is 20nm.
[0054] Step 2: Add deionized water to a vertical ball mill, then add dispersant ammonium citrate to the deionized water, add nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder and zirconia ball milling balls, and ball mill for 12 hours to obtain a uniform slurry, wherein: the amount of deionized water is twice the total mass of the nano-powder, the amount of ammonium citrate is 0.5% of the total mass of the nano-powder, the diameter of the zirconia grinding balls is 3 mm and 5 mm, the mass ratio is 6:4, and the mass of the zirconia grinding balls is 2.5 times the total mass of the nano-powder.
[0055] Step 3: Add gum arabic as a binder to the uniform slurry obtained in step 2 and then ball-mill for 0.5 h to obtain a uniform slurry, wherein the amount of gum arabic is 1.0% of the total mass of the nanopowder.
[0056] Step 4: Add the slurry obtained in step 3 into the agitator, and obtain the agglomerate powder by spray granulation, wherein: the agitator parameter is 15 rpm, the spray granulation parameters are: the inlet air temperature is 245°C, the outlet air temperature is 120°C, the needle passing frequency is 10 times per minute, and the peristaltic pump rate is 40 rpm.
[0057] Step 5: The agglomerate powder obtained after spray granulation in step 4 is screened and screened with three specifications of 400 mesh, 200 mesh and 100 mesh. The three specifications of powder are mixed in a mass ratio of 2:2:6 and wet bag cold isostatic pressing is performed under a pressure of 200Mpa. The pressure is maintained for 120s to reduce the pre-pressing process in the early stage to obtain a target embryo with a diameter of 80mm and a height of 110mm. The particle size ratio can be appropriately changed according to different process requirements.
[0058] Step 6: Use a box-type sintering furnace to sinter the target green body, raise the temperature to 350°C (debinding temperature) at 5°C / min and keep it for 300 minutes, then raise the temperature to 1100°C at 5°C / min and keep it for 180 minutes, and finally raise the temperature to 1400°C (synthesis temperature) at 5°C / min and keep it for 480 minutes, then slowly cool it to room temperature to obtain the SETDL high entropy zirconate target.
[0059] Step 7: Use 40-200 mesh silicon carbide sandpaper to grind and polish the surface of GH4169 nickel-based high-temperature alloy, and then use 60 mesh brown corundum to sandblast the surface of the substrate to make it have a certain surface roughness, and then use anhydrous ethanol and acetone to ultrasonically clean it for 30 minutes respectively, and after drying, use supersonic flame spraying technology to prepare NiCrAlY alloy bonding layer on its surface. The bonding layer preparation parameters are: spraying distance 240mm, powder feeding rate 30g / min, carrier gas flow 5NLPM, shielding gas flow 360NLPM, fuel gas flow 180NLPM, oxygen flow 240NLPM, and the thickness of the bonding layer is 100μm.
[0060] Step 8: The high entropy target sintered in step 6 is deposited on the surface of the bonding layer prepared in step 7 by EB-PVD to obtain the SETDL EB-PVD ceramic coating. The preparation parameters of the EB-PVD coating are: substrate temperature is 650°C, target-substrate distance is 250mm, incident angle is set to 45°, electron acceleration voltage is 20kV, vacuum degree is less than 1×10 -2 Pa, the deposited coating thickness is 200 μm.
[0061] In this embodiment, the macroscopic structure of the target after sintering is as follows: Figure 2 As shown by Figure 2 It can be seen that the macroscopic size meets the requirements and the surface quality is good; the cross-sectional structure diagram of the target is as follows Figure 3 As shown by Figure 3 It can be seen that the pores are evenly distributed, the pore size is evenly distributed, and there are no obvious defects inside; the surface morphology and energy spectrum of the molten pool solidified after the target material evaporates are as follows Figure 4 As shown by Figure 4 It can be seen that the melting effect of the molten pool after electron beam melting is better, the molten droplets are uniform without obvious cracks, and the elements are evenly distributed; the XRD comparison of the target molten pool, coating, and original target is shown in Figure 5 As shown by Figure 5 It can be seen that the phase structure does not change before and after deposition, and the phase structure is stable; the cross-sectional view of the coating is as follows Figure 6 As shown by Figure 6 It can be seen that the coating presents a standard columnar crystal structure, the overall quality is good, and there are no obvious defects; the coating surface is as follows Figure 7 As shown by Figure 7It can be seen that the surface quality is smooth and dense, with low roughness; the target material density and volume shrinkage are shown in Table 1.
[0062] Table 1
[0063]
[0064] Embodiment 2:
[0065] This embodiment provides a method for preparing an ultra-high temperature EB-PVD thermal barrier coating, which is achieved by the following steps:
[0066] Step 1: According to (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7, nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are weighed, wherein: the particle size of the nano Sm2O3 powder is 20nm; the particle size of the nano Eu2O3 powder is 20nm; the particle size of the nano Tb2O3 powder is 20nm; the particle size of the nano Dy2O3 powder is 20nm; the particle size of the nano Lu2O3 powder is 20nm; the particle size of the nano ZrO2 powder is 20nm.
[0067] Step 2: Add deionized water to a vertical ball mill, then add dispersant ammonium citrate to the deionized water, add nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder and zirconia grinding balls, and ball mill for 10 hours to obtain a uniform slurry, wherein: the amount of deionized water is twice the total mass of the nano-powder, the amount of ammonium citrate is 0.5% of the total mass of the nano-powder, the diameter of the zirconia grinding balls is 3 mm and 5 mm, and the mass of the zirconia grinding balls is 2.5 times the total mass of the nano-powder.
[0068] Step 3: Add gum arabic as a binder to the uniform slurry obtained in step 2 and then ball-mill for 0.5 h to obtain a uniform slurry, wherein the amount of gum arabic is 1.0% of the total mass of the nanopowder.
[0069] Step 4: Add the slurry obtained in step 3 into the agitator and obtain the agglomerate powder by spray granulation, wherein: the agitator parameter is 20 rpm, the spray granulation parameters are: the inlet air temperature is 220°C, the outlet air temperature is 100°C, the needle passing frequency is 15 times per minute, and the peristaltic pump rate is 35 rpm.
[0070] Step 5: The agglomerate powder obtained after spray granulation in step 4 is screened and screened with three specifications of 400 mesh, 200 mesh and 50 mesh. The three specifications of powder are mixed in a mass ratio of 3:3:4 and then wet-bag cold isostatic pressing is performed under a pressure of 200 MPa. The pressure is maintained for 150 seconds to reduce the pre-pressing process in the early stage to obtain a target embryo with a diameter of 80 mm and a height of 110 mm. The particle size ratio can be appropriately changed according to different process requirements.
[0071] Step 6. Sinter the target green body in a box-type sintering furnace, raise the temperature to 350°C (debinding temperature) at 5°C / min and keep it for 300min, then raise the temperature to 1100°C at 5°C / min and keep it for 250min, finally raise the temperature to 1400°C (synthesis temperature) at 5°C / min and keep it for 600min, then reduce the temperature to 800°C at 2°C and keep it for 200min, and then slowly reduce it to room temperature to obtain the SETDL high entropy zirconate target. The density and volume shrinkage of the target are shown in Table 2.
[0072] Step 7: After grinding and polishing the surface of GH4169 nickel-based high-temperature alloy with 40-200 mesh silicon carbide sandpaper, use 60 mesh brown corundum to sandblast the surface of the substrate to make it have a certain degree of roughness, and then use anhydrous ethanol and acetone to ultrasonically clean it for 30 minutes respectively, and after drying, use supersonic flame spraying technology to prepare a PtAl alloy bonding layer on its surface. The bonding layer preparation parameters are: spraying distance 240mm, powder feeding rate 25g / min, carrier gas flow rate 8NLPM, shielding gas flow rate 360NLPM, fuel gas flow rate 180NLPM, oxygen flow rate 240NLPM, and the thickness of the bonding layer is 150μm.
[0073] Step 8: The high entropy target sintered in step 6 is deposited on the surface of the bonding layer prepared in step 7 by EB-PVD to obtain the SETDL EB-PVD ceramic coating. The preparation parameters of the EB-PVD coating are: the substrate temperature is 600°C, the target-substrate distance is 280mm, the incident angle is set to 45°, the electron acceleration voltage is 25kV, and the vacuum degree is less than 1×10 -2 Pa, the deposited coating thickness is 200 μm.
Claims
1. A method for preparing an ultra-high temperature EB-PVD thermal barrier coating, characterized in that The method comprises the following steps: Step 1: Add zirconium oxide grinding balls and appropriate amount of deionized water to the vertical ball mill, then add dispersant to the deionized water, and after the dispersant is completely dissolved, follow the (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7, add nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder, and then ball mill for a period of time, add a binder and continue to ball mill for a period of time to obtain a uniform slurry, wherein: the amount of deionized water is 0.5 to 3 times the total mass of the nano powder, the amount of the dispersant is 0.03 to 6% of the total mass of the nano powder, and the amount of the binder is 0.1 to 10% of the total mass of the nano powder; Step 2: The slurry obtained in step 1 is subjected to spray granulation to obtain micrometer-sized nanostructured spherical rare earth oxide powder; Step 3, the YSZ agglomerated powder obtained in step 2 is screened according to the particle size, the spherical powders with different particle sizes after screening are proportioned, and then pressed by cold isostatic pressing method to obtain target embryos with different porosities, wherein: the screening specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, and the mass ratio is 2-6:1-3:1-5; Step 4: Sintering the target green body to obtain a high entropy zirconate EB-PVD target, wherein the sintering mechanism is: first, increasing the temperature to 350°C at 1-10°C / min and keeping it for 300-420min, then increasing the temperature to 1100°C at 1-10°C / min and keeping it for 180-250min, then increasing the temperature to 1400°C at 1-10°C / min and keeping it for 480-600min, and finally, reducing the temperature to room temperature; Step 5: grinding and polishing the surface of the high-temperature alloy substrate to make it smooth, then sandblasting it, and then using acetone and ethanol to ultrasonically clean it, and after drying, using thermal spraying technology to prepare an alloy bonding layer on its surface; Step 6: Deposit the high entropy zirconate EB-PVD target on the surface of the MCrAlY alloy bonding layer obtained in step 5 by using a vapor deposition method to form a high entropy zirconate ceramic coating.
2. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The particle sizes of the nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are all 5 to 90 nm; the dispersant is one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, ammonium citrate, sodium citrate, polyvinyl alcohol and polyethylene glycol; the binder is one of gum arabic, polyvinyl alcohol, carboxymethyl cellulose and ethyl silicate; the diameter of the zirconia grinding balls is 2 to 10 mm, the amount of the zirconia grinding balls is 1 to 5 times the total mass of the nano powder, the total ball milling time is 6 to 24 hours, and the number of revolutions is 300 to 1000 revolutions per minute.
3. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The parameters of spray granulation are as follows: the inlet air temperature is set at 200-250°C, the outlet air temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45 r / min, and the needle passing speed is set at 10-15 t / min.
4. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that During the pressing process, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 s.
5. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The cold isostatic pressing method uses a wet bag cold isostatic pressing, a dry bag cold isostatic pressing, and a press pre-pressing molding method.
6. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The high-temperature alloy substrate is one of nickel-based, cobalt-based and iron-based high-temperature alloys.
7. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The thermal spraying technology is one of atmospheric plasma spraying, low-pressure plasma spraying and supersonic flame spraying.
8. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The alloy bonding layer is one of NiCrAlY, CoCrAlY and NiCoCrAlY.
9. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The parameters in the preparation process of the high entropy zirconate ceramic coating are as follows: the substrate temperature is heated from room temperature to 600-850°C, the electron acceleration voltage is 20-25 kV, and the vacuum degree is less than 1×10 -2 Pa, the deposition rate is 1-10 μm / min, and the deposition coating thickness is 100-500 μm.
10. The method for preparing the ultra-high temperature EB-PVD thermal barrier coating according to claim 1, characterized in that The vapor deposition method is one of electron beam physical vapor deposition and physical vapor deposition.
Citation Information
Patent Citations
Lanthanum zironate based ceramic target material for electron beam physical vapor deposition and preparation method thereof
CN107903060A
YSZ-rare earth zirconate thermal barrier coating of gradient structure and preparation method thereof
CN108441807A
High-entropy oxide ultra-high-temperature thermal barrier coating prepared through EB-PVD technology and method thereof
CN114000107A
Zirconate ceramic material as well as preparation method and application thereof
CN115093218A
Lanthanum gadolinium samarium-based high-entropy thermal barrier coating and preparation method thereof
CN115161595A
Cited By
Nano-structure thermal barrier coating with low thermal conductivity, high thermal expansion coefficient and long service life and preparation method of nano-structure thermal barrier coating
CN121085316A